MENGENAL FIDUCIARY DUTY DAN BUSINESS JUDGMENT RULE DIREKSI DAN KOMISARIS - Sandra Dewi; Hasnati Hasnati (Ensiklopedia Social Review, 2019)
To find out the Fiduciary Duty and Business Judgment Rule for Directors and commissioners, it must be considered the basic provisions governing the duties of management, obligations and especially the responsibilities of the directors of limited liability companies in the Company Law. Regarding the management of the company regulated in the Company Law with fiduciary duty and business judgment rule, it can be said that the basic provisions governing fiduciary duty and the business judgment rule in the Company Law can be found in general rules or provisions in Article 97 of Company Law. . These general provisions then spread in various other articles in the Company Law. Keywords: Fiduciary Duty, Business Judgment Rule, Directors and Commissioner